The increase in non-marital childbearing and its link to educational expansion - Schor Christine; Jalovaara Marika (Sage Publications Ltd., 2022)
The increase in non-marital childbearing has coincided with educational expansion, although non-marital childbirths are more common among the low-educated population. This article quantifies the contribution of changes in education-specific rates of non-marital childbearing and educational distribution of parents to increases in non-marital childbearing among Finnish first-time parents over the period 1970–2009. Using Finnish register data on first-time mothers (N = 112,730) and fathers (N = 108,812), the study decomposes changes in the proportion of non-marital first childbearing in pairwise comparisons of successive decades for four educational segments: low educated (International Standard Classification of Education (ISCED) 0–2), medium educated (ISCED 3–4), lower tertiary educated (ISCED 5–6) and upper tertiary educated (ISCED 7–8). The findings show that the increase in non-marital first-time births was mainly attributable to the large population of medium-educated women and men and the growing segment of lower tertiary-educated women. The highest proportion of non-marital first-time childbearing remained among the low-educated population, but diminishing group size meant their overall contribution was small. The growing upper tertiary-educated population increased its contribution to non-marital childbearing but still exhibited the lowest non-marital childbearing rates. We conclude that the medium-educated population merits increased scholarly attention for its important contribution to population-level changes.